Empirical Analysis of Fintech and Marketing Strategy Impact on MSME Development in Magelang - Erni Puji Astutik; Retnosari (Institut Bisnis dan Informatika Kesatuan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in regional economic growth, yet their development is often constrained by limited access to financial services and ineffective marketing strategies. This study aims to examine the influence of financial technology and marketing strategies on MSME development in Magelang Regency. A quantitative approach was employed using primary data collected through questionnaires distributed to MSME actors who utilize fintech services. The data were analyzed using multiple linear regression to test the effect of independent variables on MSME development. The results indicate that financial technology has a significant positive effect on MSME growth, particularly through improved transaction efficiency, payment security, and access to financial services. In contrast, marketing strategy does not show a statistically significant impact, suggesting that current practices remain relatively simple and limited in scope. However, the interaction between fintech and marketing holds potential to enhance brand awareness and consumer trust, particularly through digital payments and online marketplaces. The study concludes that fintech adoption is a key driver of MSME development, while marketing strategies require further strengthening. Policymakers and business stakeholders are encouraged to promote fintech literacy and digital marketing training to support sustainable MSME growth.